THE REPRESENTATION OF WOMEN IN PRINT ADVERTISEMENTS OF AUTOCAR MAGAZINES(A Systemic Linguistic of Selected Print Autocar Advertisements) - Harry Rakhman Martakusuma, - (2011)
The present study investigates the representations of women in selected print advertisements in Autocar Magazine. Three print advertisements in Autocar Magazines were selected as the primary data to be analyzed. The selected advertisements were categorized only for car advertisements that used women as their models. This study applied descriptive-qualitative method and semiotic tool to reveal the representations of women in the selected advertisements. The women images were analyzed using Kress and van Leeuwen's visual text analysis (1990). On the other hand, the verbal texts of the selected advertisements were analyzed using a Hallidayan functional grammar framework (2004). The findings reveal that the women images in the selected advertisements were represented the car for their segmented audiences. The models are not represented to have a social relation with their target audiences. They also represented as, beautiful, attractive and well taken in terms of their faces, bodies, and hair which are implied to attract the readers. The results of this study are expected to contribute some references about women which are used as models in print advertisements and their meaning presented on the advertisements.